The Use of Panax Ginseng to Reduce the Cardiotoxicity of Doxorubicin and Study its Effect on Modulating Oxidative Stress, Inflammatory, and Apoptosis Pathways - Al-Hussaniy, Hany Akeel; Al-Kuraishy , Hayder M.; Abdulameer, Abdul-Ghaffar A. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Doxorubicin (DOX) is a broad-spectrum anti-cancer drug that is used to treat a variety of cancers, including blood cancers such as leukemia and solid tissue cancers. However, its use some time limited because of its cardiotoxicity. OBJECTIVE: The objective of the study was to determine the cardioprotective effect of ginseng in the case of cardiotoxicity caused by doxorubicin therapy. Methods: Thirty experimental animals (male Sprague Wistar rats) were used in this research and they were separated into three groups: Rats in Group I (n# = 10) were given distilled water plus normal saline, rats in Group II (n# = 10) were given distilled water plus doxorubicin, and rats in Group III (n# = 10) were given Panax ginseng plus doxorubicin. Serum concentration, malondialdehyde (MDA), glutathione reductase (GSH), lipid peroxidase (LPO), TNF (ng/L), cardiac troponin (ng/L), brain natriuretic peptide BNP(g/L), and caspase-3 (pmol/L) levels were measured in all groups. RESULTS: Doxorubicin caused substantial cardiotoxicity as a result of a significant increase in the elevation of cTnI to 40.09 ± 6.67 (ng/L). In addition, MDA, LPO, TNF-α, and caspase-3 levels were increased in doxorubicin group compared to the control group p < 0.05. Panax ginseng reduced cardiac troponin (cTnI) However, its effect on reduction of BNP levels insignificantly compared to the doxorubicin group p = 0.06. Panax ginseng reduced LPO and MDA and raised the antioxidant potential biomarker GSH significantly compared to the doxorubicin group p < 0.05. Panax ginseng significantly reduced inflammatory (TNF-α) and apoptotic (caspase-3) biomarkers when compared to the doxorubicin group. CONCLUSIONS: According to the findings of this study, Panax ginseng suppresses reactive oxygen species and inflammatory and apoptotic pathways in experimental rats, thereby preventing doxorubicin-induced cardiovascular events.